Evaluating the implementation of the Pan-European Criteria and indicators for sustainable forest management – A SWOT analysis. (January 2016) - Baycheva-Merger, Tanya; Wolfslehner, Bernhard
Highlights: We analyze SWOT factors of the implementation of the pan-European C&I for SFM. C&I have been useful in SFM monitoring, reporting and assessment. C&I have supported forest policy development, dialogue and communication. Further improvement is required in C&I information transfer and scientific research. More efforts needed as regards to capacity building and cross-sectoral collaboration. Abstract: Since the beginning of the 1990s, the notion of Criteria and Indicators (C&I) as a framework for evaluating sustainable forest management (SFM) rapidly gained interest. There have been several international processes and initiatives related to the development of C&I as a tool for defining SFM and measuring its progress. In Europe, a set of criteria and indicators was developed in 1998 by FOREST EUROPE, former Ministerial Conference on the Protection of Forests in Europe (MCPFE). However, until recently, insufficient information has been available on how the pan-European C&I have been used and what their real impact has been. A recent study 1 (the "CI-SFM" project) conducted by the European Forest Institute (EFI) is the first effort to collect information on the implementation of the pan-European C&I in the 46 signatory states of the FOREST EUROPE process. The study analyzed how and to what extent the pan-European C&I have been used at the pan-European and national levels, investigated challenges and gaps in its implementation, and explored opportunities for further improvement. However, there is need for a prioritization and a more specific query on the factors influencing the implementation of the pan-European C&I in order to identify the major cornerstones for further use and priority areas for action. Thus, building on the findings from the EFI study, the main objective of this article is to analyze the SWOT factors (Strengths (S) – Weaknesses (W) – Opportunities (O) – Threats (T)) of the pan-European C&I in order to determine and prioritize the major constraints and future possibilities of their use and implementation. The results show that in order to consider the pan-European C&I as a powerful tool for promoting sustainable forest management, both at national, sub-national and pan-European levels, a number of factors (e.g. data availability and quality, cross-sectoral communication, conceptual validity, clear objectives, capacity building) that influence the implementation of the indicator set require further research and action by policy makers and relevant stakeholders.